(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Organizations today are constantly focusing on increasing their competitiveness. One of the ways of increasing competitiveness is by tapping the creative potential of the employees. One of the best ways in which organizations’ can capture their employees’ creativity is by creating a climate that nurtures creativity. Having a creative working climate nourishes and creates a suitable working culture that enhances the creative spark of the employees. Based on this premise, the study attempted to determine the attributes that facilitate the development of a creative climate and to examine the difference between the present state and the desired state of organization creative climate attributes. A sample of 78 marketing professionals were taken from media and advertising firms and quadrant analysis was employed for analysis. The results highlighted the attributes that require increased attention from organizations to enhance employee creativity. The paper also discusses the managerial implications and directions for future research.